Rainmaking conversations : influence, persuade, and sell in any situation - Schultz, Mike, 1974-; Doerr, John E. (Hoboken, N.J. : Wiley, 2011)
'Master the conversations that can make or break everything in complex sales Every conversation presents opportunity to find new opportunities, win new customers, and increase sales. Rainmaking Conversations gives you a proven system to uncover and leverage these opportunities and achieve maximum revenue results, robust relationships, and deep trust. Rainmaking Conversations is the first book to offer a research-based selling approach that can help you master the art of the sales conversation. From start to finish of each conversation, you'll make every client contact you have count towards developing sustainable sales success. Build rapport and trust from the first handshake Learn the 7 keys for leading successful business development conversations Develop winning value propositions that gets prospects excited to buy Craft winning solutions and close the deal Speed up the sales cycle Lead conversations that persuade and influence the prospect to choose you Rainmaking Conversations walks you through RAIN SellingSM-a world-class sales methodology that has helped tens of thousands of people lead powerful sales conversations and achieve breakthrough sales performance.'--
Machine generated contents note: 1.Introduction -- 2.The Most Important Conversation You'll Ever Have -- 3.Goal and Action Planning: Making the Most Rain -- 4.Understanding and Communicating Your Value Proposition -- 5.Rapport -- 6.Aspirations and Afflictions -- 7.Impact -- 8.New Reality -- 9.Balancing Advocacy and Inquiry -- 10.Digging Deep into Needs: The Five Whys -- 11.16 Principles of Influence in Sales -- 12.Tips for Leading Rainmaking Conversations -- 13.Prospecting by Phone: Creating Rainmaking Conversations -- 14.Handling Objections -- 15.Closing Opportunities, Opening Relationships -- 16.What You Need to Know to Sell -- 17.Planning Each Rainmaking Conversation -- 18.How to Kill a Sales Conversation -- 19.Putting RAIN in Your Forecast.
Includes bibliographical references and index.
Keywords: Selling -- Psychological aspects; Persuasion (Psychology); Influence (Psychology)